2013
DOI: 10.1016/j.java.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The Healthcare and Technology Synergy (HATS) Framework for Comparative Effectiveness Research as Part of Evidence-Based Practice in Vascular Access

Abstract: The development of frameworks for nursing research, practice, and education is in its infancy. The focus in clinical research has commonly been on the variables patient and practice, not on the significant variable, technology products. However, in interventional and medical cardiology and orthopedic surgery, for example, products used are significant variables that affect clinical outcomes and subsequent recalls. The purpose of this article is to introduce the Healthcare and Technology Synergy (HATS) framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…HCPs are expected to use EBP as a standard approach to daily practice [7][8][9], integrating research, patient preferences, clinical expertise, and innovative technologies [10,11]. However, the implementation of EBP remains a controversial process [12,13], and not all HCPs are convinced that it improves the quality of care [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…HCPs are expected to use EBP as a standard approach to daily practice [7][8][9], integrating research, patient preferences, clinical expertise, and innovative technologies [10,11]. However, the implementation of EBP remains a controversial process [12,13], and not all HCPs are convinced that it improves the quality of care [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The search strategy retrieved a total of 18,299 references (16,795 from databases and 1504 from other sources), and after removing duplicates, we included 12,948 references (11,469 from databases and 1479 from other sources) that will be analyzed on the titles and abstracts by 2 independent researchers (Table 1). In the second phase, full-text papers will be retrieved from the references and analyzed based on the inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, the homogeneity of the sample could be considered an advantage, being reduced the bias observed in the central elements related to effectiveness of CVC clinical research (product, practice and patient), frequently reported in multicenter studies [18]. Several studies does not report CVC-management dynamics based on the use of chlorohexidine 2% NC hub disinfection 15", CVC-flushing frequency report, positive pressure and push-pause techniques [19]; being the quality of the research limited to the product.…”
Section: Potential Directions Of the Study And Limitationsmentioning
confidence: 99%